ANALYSIS OF PRODUCTION FACTORS AREN GENJAH (Arenga Pinnata) IN DELI SERDANG DISTRICT - Junaidi; Yusniar Lubis; M. Akbar Siregar (RADJA PUBLIKA, 2024)
This research aims to analyze the factors that influence production (capital, labor, product quality and land area) on the production volume of early maturing sugar palm farmers in Deli Serdang. This research was conducted using a survey method and determining the research location purposively. The sample selection method uses the Slovin formula by taking samples from farmers so that the sample used is 102 respondents. The analysis used is the Cobb-Douglas production function. The research results show that the production factor that has a real influence on the production of early maturing sugar palm is labor.